2023
DOI: 10.1155/2023/8567870
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Caring Behavior and Caring Burden and Their Associated Factors among Nurses Who Cared for Patients with COVID-19 in East Guilan, the North of Iran

Abstract: Background. Nurses experience caring burdens, which can affect their caring behaviors. Caring for highly infectious patients, in particular COVID-19, is a new phenomenon and little is known about it. Considering that caring behaviors can be influenced by various factors and cultural differences of the society, it is necessary to conduct studies about caring behaviors and caring burdens. Thus, this study aimed to determine caring behavior and caring burden and their relationship with some associated factors amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…This result suggests that the increase in the time spent in the profession in direct proportion to the age of the nurses may have improved their knowledge-skill levels and positively affected their care-giving behaviors. Unlike the result of this study, similar studies in the literature found that age variable did not affect the mean scores of "knowledge-skill" subscale 38,39,[41][42][43][44][45] .…”
Section: Discussioncontrasting
confidence: 79%
“…This result suggests that the increase in the time spent in the profession in direct proportion to the age of the nurses may have improved their knowledge-skill levels and positively affected their care-giving behaviors. Unlike the result of this study, similar studies in the literature found that age variable did not affect the mean scores of "knowledge-skill" subscale 38,39,[41][42][43][44][45] .…”
Section: Discussioncontrasting
confidence: 79%
“…Pandemics, a global health problem, are a threat to nurses and all other health workers. 6 Intensive care nurses spend more time with patients and are directly responsible for patient care. 7 Global health institutions are aware of the necessity of nursing care in their efforts to prevent and respond to epidemics, and underline that its importance is increasing day by day.…”
Section: Introductionmentioning
confidence: 99%